2003
DOI: 10.1029/2002gl015839
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling of slip spatial complexities for the 1979 Imperial Valley, California, earthquake

Abstract: [1] Finite-fault source inversions reveal the spatial complexity of earthquake slip or prestress distribution over the fault surface. In this paper we discuss a stochastic model that reproduces the spatial variability and the long-range spatial correlation of the slip distribution of the 1979 Imperial Valley earthquake. We have found that stochastic models based on non-Gaussian distributions are better suited to describe the spatial variability of the slip amplitude over the fault. We also show that a stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 23 publications
2
81
2
Order By: Relevance
“…Recent studies have clarified systematic features of earthquake source via the scaling of slip distributions (Somerville et al, 1999;Mai and Beroza, 2000) or via slip complexity (Mai and Beroza, 2002;Lavallee and Archuleta, 2003). Waveform inversions and strong motion simulations show that asperities within the rupture area control the ground motion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clarified systematic features of earthquake source via the scaling of slip distributions (Somerville et al, 1999;Mai and Beroza, 2000) or via slip complexity (Mai and Beroza, 2002;Lavallee and Archuleta, 2003). Waveform inversions and strong motion simulations show that asperities within the rupture area control the ground motion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Both can be non uniform. Slip distributions inferred from seismological and geodetic data provide a valuable constraint on possible stochastic parameterizations of stress drop [Mai and Beroza, 2002;Lavallée and Archuleta, 2003]. Fracture energy might be the only dynamic parameter that can be robustly inferred from frequency-limited strong motion data [Guatteri and Spudich, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Lavallée and Archuleta (2003) found that the slip distribution of the 1979 Imperial Valley earthquake could be well modeled with a stochastic model assuming power law of k -n , where k is the wavenumber. A stochastic approach has to be taken in the following two cases.…”
Section: Source Models Of the 2010 Canterbury Earthquakementioning
confidence: 99%